Safety and pitfalls in frozen elephant trunk implantation - Damberg, Anneke; Schälte, Gereon; Autschbach, Rüdiger; Hoffman, Andras (Annals of Cardiothoracic Surgery; Vol 2, No 5 (September 01, 2013): Frozen Elephant Trunk, 2013)
The frozen elephant trunk (FET) procedure, or open stent grafting, is a tool for the combined open and endovascular treatment via a median sternotomy of extensive aortic disease involving both aortic arch and descending thoracic aorta. The technique aims to stabilize the maximum extent of the thoracic aorta in one step, with the goal of either rendering a secondary intervention to the downstream aorta unnecessary or producing an easy landing zone for secondary thoracic endovascular aortic repair (TEVAR) or open surgery. Even though large case series have reported good results, we still have no conclusive evidence as to which patients and what kind of pathologies benefit from this technique. The surgical sequences described for total arch replacement with the FET procedure are just as varied as the associated devices and indications. This article focuses on important perioperative and surgical aspects, as well as potential complications during FET procedures.